2014
DOI: 10.1111/cfs.12183
|View full text |Cite
|
Sign up to set email alerts
|

Home sweet home? Professionals' understanding of ‘home’ within residential care for unaccompanied youths in Sweden

Abstract: A B S T R AC TThe number of unaccompanied minors arriving in Sweden continues to rise. The majority are placed in residential care units. This qualitative study aims to increase the understanding given by the professionals to the concept of 'home' within the framework of residential care for unaccompanied young people. Data are based on participatory observations at two residential care units, followed up by individual interviews with staff. The findings confirm that the concept of home has a complex meaning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
0
16
0
4
Order By: Relevance
“…Several studies on refugee children and UMs have dealt with the notion of resilience versus vulnerability (Derluyn, Broekaert & Schuyten 2008;Eide & Hjern 2013;Luster et al 2010;Nardone & Correa-Velez 2015;Wallin & Ahlström 2005). It has been shown that the introductory stage, namely, how these children are received and how the asylum process takes place, has a very important impact on the well-being of these children (Çelikaksoy & Wadensjö 2017a;Söderqvist, Sjöblom & Bulow 2014;Wimelius, Joakim & Mehdi 2016). Some of the important influences identified in the Nordic countries are related to close contacts with persons from the society of the destination country and the time of waiting (Honkasalo 2017).…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on refugee children and UMs have dealt with the notion of resilience versus vulnerability (Derluyn, Broekaert & Schuyten 2008;Eide & Hjern 2013;Luster et al 2010;Nardone & Correa-Velez 2015;Wallin & Ahlström 2005). It has been shown that the introductory stage, namely, how these children are received and how the asylum process takes place, has a very important impact on the well-being of these children (Çelikaksoy & Wadensjö 2017a;Söderqvist, Sjöblom & Bulow 2014;Wimelius, Joakim & Mehdi 2016). Some of the important influences identified in the Nordic countries are related to close contacts with persons from the society of the destination country and the time of waiting (Honkasalo 2017).…”
Section: Literature Overviewmentioning
confidence: 99%
“…Some of the important influences identified in the Nordic countries are related to close contacts with persons from the society of the destination country and the time of waiting (Honkasalo 2017). It is found that these contacts are very important for the adjustment process of this group, whereby they learn how to navigate the new society (Iveroth 2015; Ombudsman for Children in Sweden 2016; Söderqvist, Sjöblom & Bulow 2014;Stretmo & Melander 2013). The situation of youth in the labour market is thoroughly covered in a well-established literature for native-born individuals, while only a few studies focus on refugee youth with large-scale data that enable the decomposition of this group.…”
Section: Literature Overviewmentioning
confidence: 99%
“…In more recent work, Wade, et al (2012) emphasise how problems can arise when UAMs are placed in non-specialist provision, causing confusion for existing non-UAM residents. Furthermore, a Swedish study by Söderqvist et al (2016) highlighted the challenges for residential staff in creating an 'ordinary home' for UAMs given their surveillance role and the use of legal mandates that were not designed with this population in mind.…”
Section: Alternatives To Foster Carementioning
confidence: 99%
“…Uklare formål kan gi ikke-reflektert praksis, det vil si en praksis der profesjonsutøverne handler ut fra egne, selvfølgeliggjorte forståelser og forestillinger om hva omsorgsarbeidet er og bør vaere. Dette beskrives blant annet i en svensk studie av omsorgsarbeid med enslige mindreårige flyktninger i bofellesskap (Söderqvist, Sjöblom og Bülow 2016). Også her finner forskerne at mange av de ansatte anser hjemmet som ideal, men uten at de synes å ha en eksplisitt oppfatning av hva dette innebaerer.…”
Section: Uklare Formål Og Omsorgspraksisunclassified